A stealth coating and a method for preparing the same
Patent Information
- Application Number
- CN202512001857.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-29
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-12-29
AI Technical Summary
然而,纳米石墨烯固有的疏水疏油特性导致其与成膜物相容性差,而且密度极轻,存在分散困难、分散体系不稳定等问题,难以直接应用于吸波涂层
本发明利用活化石墨烯表面的二氧化硅包覆层与内部二氧化钛复配实现渐变匹配,使雷达波高效耦合进入材料内部,提升了宽频段的电磁波吸收效率,而内部负载的二氧化钛与磁性镍锌铁氧体形成电磁损耗网络,通过介电极化与磁滞损耗进一步协同耗散宽频段(2~18GHz)电磁能量,显著提升吸波效能。
Smart Images

Figure CN121610166B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating technology, and in particular to a stealth coating and its preparation method. Background Technology
[0002] Stealth technology reduces the probability of a target being detected by surveillance equipment by controlling and reducing the characteristic signals of the device. As a crucial pathway in stealth technology, the development of stealth coatings has shown broad application prospects in the defense, military, and aerospace fields due to their ease of application, cost-effectiveness, and adaptability. Currently, stealth coatings are widely used in aerospace and military equipment, encompassing various types such as electromagnetic stealth, infrared stealth, visible light stealth, and acoustic stealth.
[0003] As environments become increasingly complex, single-function stealth materials are no longer sufficient to meet the demands, making radar- and infrared-compatible stealth materials a research hotspot. The core of radar stealth lies in reducing the radar reflectivity of the target object, while infrared stealth requires increasing infrared reflectivity. Traditional single-function materials struggle to simultaneously satisfy the requirements of wideband radar wave absorption and low infrared emissivity.
[0004] Currently, research on stealth coatings mainly focuses on the field of microwave absorbing materials. Nanomaterials, with their advantages of wide bandwidth, good compatibility, light weight, and thin thickness, have become an ideal choice. For example, graphene nanoparticles, as one-dimensional tubular structures, have high-frequency broadband absorption characteristics and are widely used in microwave absorbing materials. However, the inherent hydrophobic and oleophobic properties of graphene nanoparticles lead to poor compatibility with film-forming materials, and their extremely low density results in problems such as difficulty in dispersion and instability of the dispersion system, making it difficult to directly apply them to microwave absorbing coatings.
[0005] Existing stealth coatings are insufficient to effectively cover the absorption requirements of broadband radar bands; moreover, achieving compatibility between low infrared emissivity and high radar transmittance remains a technical challenge. The contradiction between the two performance characteristics restricts the development of stealth materials and has become a technical difficulty in the research and development of broadband stealth coatings. Summary of the Invention
[0006] The purpose of this invention is to address the shortcomings of existing technologies by proposing a stealth coating and its preparation method.
[0007] A stealth coating comprises, by weight, the following raw materials: 40-60 parts aliphatic polyurethane resin, 10-30 parts room temperature vulcanized phenyl silicone rubber, 1-2 parts silane coupling agent, 1-5 parts hollow phenolic microspheres, 1-3 parts infrared reflectance enhancer, 1-2 parts magnetic nano-ferrite, 1-2 parts nano-silicon carbide, 7-17 parts activated graphene, 1-2 parts wetting agent, 1-2 parts defoamer, 1-2 parts plasticizer, 1-5 parts crosslinking agent, 1-2 parts dispersant, and 80-150 parts solvent; the activated graphene is obtained by mixing titanium dioxide-supported graphene with tetraethyl orthosilicate and silane coupling agent in an alkaline environment.
[0008] Preferably, the defoamer is an organosilicone defoamer.
[0009] Preferably, the plasticizer is a phosphate plasticizer.
[0010] Preferably, the infrared reflectance enhancer is boron nitride nanosheets with a particle size of 100-300 nm.
[0011] Preferably, the magnetic nanoferrite is NiZnFe2O4 with a particle size of 100-500 nm.
[0012] Preferably, the crosslinking agent is a silanol condensation type crosslinking agent, and more preferably dimethyldimethoxysilane.
[0013] Preferably, the dispersant is a polycarboxylate dispersant.
[0014] Preferably, the solvent includes: ethyl acetate, dipropylene glycol dimethyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, and water; the mass ratio of ethyl acetate, dipropylene glycol dimethyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, and water is 20-30:5-15:5-15:10-18:20-40.
[0015] Preferably, activated graphene is prepared by the following steps: tetraethyl orthosilicate is added to an aqueous ethanol solution and stirred until homogeneous; titanium dioxide-supported graphene is added to the solution; the pH of the system is adjusted to 8-9; and the solution is stirred at 30-40°C for 10-20 hours; then a silane coupling agent is added to the solution; the solution is stirred at 50-60°C for 1-2 hours; the solution is then centrifuged, washed, and vacuum dried.
[0016] More preferably, the silane coupling agent is KH-550 coupling agent.
[0017] More preferably, the mass ratio of tetraethyl orthosilicate, titanium dioxide-supported graphene, and silane coupling agent is 1-5:5-10:1-2.
[0018] More preferably, titanium dioxide-supported graphene is prepared by the following steps: adding graphene oxide to water and sonicating for 20-40 min, adding nano-titanium dioxide, stirring at 60-70℃ for 1-2 h, hydrothermally treating at 200-220℃ for 10-20 h, cooling to room temperature, centrifuging, washing, and freeze-drying; holding at 700-800℃ for 10-30 min in an argon atmosphere, and then cooling to room temperature.
[0019] Specifically, the mass ratio of graphene oxide to nano-titanium dioxide is 4-8:1-3.
[0020] The preparation method of the above-mentioned stealth coating includes the following steps: adding activated graphene and dispersant to a solvent and stirring for 5-15 minutes to obtain a premix; adding aliphatic polyurethane resin, room temperature vulcanized phenyl silicone rubber, silane coupling agent, hollow phenolic microspheres, infrared reflection enhancer, magnetic nano ferrite, and nano silicon carbide to the premix and stirring for 20-40 minutes; then adding wetting agent, defoamer, plasticizer, and crosslinking agent in sequence and stirring for 20-40 minutes, and finally sieving.
[0021] Beneficial effects: This invention utilizes the silica coating layer on the surface of activated graphene to achieve a gradient matching with the internal titanium dioxide, enabling radar waves to be efficiently coupled into the material, thus improving the absorption efficiency of electromagnetic waves over a wide frequency band. The internally loaded titanium dioxide and magnetic nickel-zinc ferrite form an electromagnetic loss network, which further dissipates wide-frequency (2-18GHz) electromagnetic energy through dielectric polarization and hysteresis loss, significantly improving the absorption efficiency.
[0022] This invention uses hollow phenolic microspheres as low-density, high-porosity structural units, which work synergistically with activated graphene to construct wave-transparent channels in the coating, allowing some incident radar waves to penetrate the coating instead of being reflected, thus reducing the overall radar scattering cross section; while in the infrared band, phenyl silicone rubber works synergistically with boron nitride nanosheets and nano-silicon carbide to effectively reduce the infrared emissivity of the coating.
[0023] This invention enables most of the radar wave energy in the coating to be absorbed by the internal loss network, with a small portion transmitted through the microspheres and activated graphene, while reflection is suppressed; infrared radiation is effectively blocked, achieving spatial separation and functional decoupling of electromagnetic response, and achieving synergistic enhancement of broadband wave absorption and infrared stealth.
[0024] This invention enables multiple scattering and absorption of electromagnetic waves, resulting in a wide-bandwidth, low-mass absorbing stealth coating. This coating provides strong absorption of electromagnetic waves in the 2-18GHz frequency range and significantly reduces infrared emissivity, thereby synergistically improving stealth performance. Furthermore, the preparation method is simple and easy to operate, making it suitable for large-scale application. Attached Figure Description
[0025] Figure 1 The image shows a comparison of the average RCS values of the stealth coatings formed using the stealth coatings obtained in Example 5 and Comparative Examples 1-2.
[0026] Figure 2 The image shows a comparison of the average infrared emissivity of the stealth coatings formed using the stealth coatings obtained in Example 5 and Comparative Examples 1-2.
[0027] Figure 3 The graph shows the longest service life of the stealth coatings formed using the stealth coatings obtained in Example 5 and Comparative Examples 1-2. Detailed Implementation
[0028] The present invention will be further explained below with reference to specific embodiments.
[0029] The aliphatic polyurethane resin used below was purchased from Wuhan Quanxing New Material Technology Co., Ltd., model 8135, with a solid content of 35±2% and a viscosity (25℃) <1000CPS. The room temperature vulcanizing phenyl silicone rubber used below was purchased from Anhui Yi Silicon Industry Co., Ltd., model MY35, with a viscosity (25℃) of 6000±4000 mPa·s and a phenyl content of 2.5-20.0 mol%. The hollow phenolic microspheres (BJO-0930) used below were purchased from Guangdong Jiang Chemical Reagent Co., Ltd. The boron nitride nanosheets used below were purchased from Zhejiang Meinano Technology Co., Ltd., model AM-HBN-073-2, with an average particle size of 200 nm. The magnetic nanoferrite used below was nickel-zinc ferrite (NiZnFe2O4), purchased from Hebei Renhe Alloy Materials Co., Ltd., with an average particle size of 500 nm. The wetting agent used below was sourced from Solverodia, brand name AEROSOL OT-75. The silicone defoamer used below is from Evonik, brand name TEGO Foamex 1488. The polycarboxylate dispersant used below was purchased from Dongying Mouwang Chemical Co., Ltd.
[0030] Example 1 A stealth coating comprises the following raw materials: 40g aliphatic polyurethane resin, 10g room temperature vulcanized phenyl silicone rubber, 1g silane coupling agent KH-560, 1g hollow phenolic microspheres, 1g boron nitride nanosheets, 1g magnetic nanoferrite, 1g nano silicon carbide, 7g activated graphene, 1g wetting agent, 1g organosilicon defoamer, 1g trichloroethyl phosphate, 1g dimethyldimethoxysilane, 1g polycarboxylate dispersant, and 80g solvent.
[0031] The solvent is composed of ethyl acetate, dipropylene glycol dimethyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, and deionized water in a mass ratio of 20:5:5:10:20.
[0032] Activated graphene was prepared by the following steps: 1g of tetraethyl orthosilicate was added to 50g of 50% ethanol aqueous solution and stirred until homogeneous. 5g of titanium dioxide-supported graphene was added to the solution. The pH of the system was adjusted to 8-9 using ammonia. The solution was stirred at 30℃ for 10h at a stirring speed of 300r / min. 1g of KH-550 coupling agent was added to the solution. The solution was stirred at 50℃ for another 1h. The solution was then centrifuged, washed, and vacuum dried.
[0033] Titanium dioxide-supported graphene was prepared by the following steps: 4g of graphene oxide was added to 40g of deionized water and ultrasonically treated for 20min at a frequency of 70kHz. 1g of nano-titanium dioxide was added and stirred at 60℃ for 1h at a stirring speed of 300r / min. The mixture was then added to a high-pressure reactor and hydrothermally treated at 200℃ for 10h. After cooling to room temperature, the mixture was centrifuged, washed, and freeze-dried. The mixture was then held at 700℃ for 10min in an argon atmosphere and cooled to room temperature.
[0034] The preparation method of the above-mentioned stealth coating includes the following steps: adding activated graphene and polycarboxylate dispersant to a solvent and stirring at 500 r / min for 5 min to obtain a premix; adding aliphatic polyurethane resin, room temperature vulcanized phenyl silicone rubber, silane coupling agent KH-560, hollow phenolic microspheres, boron nitride nanosheets, magnetic nanoferrite, and nano silicon carbide to the premix and stirring at 200 r / min for 20 min; sequentially adding wetting agent, organosilicon defoamer, trichloroethyl phosphate, and dimethyldimethoxysilane and stirring at 200 r / min for 20 min; and passing the mixture through a 200-mesh sieve.
[0035] Example 2 A stealth coating comprises the following raw materials: 60g aliphatic polyurethane resin, 30g room temperature vulcanized phenyl silicone rubber, 2g silane coupling agent KH-560, 5g hollow phenolic microspheres, 3g boron nitride nanosheets, 2g magnetic nanoferrite, 2g nano silicon carbide, 17g activated graphene, 2g wetting agent, 2g organosilicon defoamer, 2g trichloroethyl phosphate, 5g dimethyl dimethoxysilane, 2g polycarboxylate dispersant, and 150g solvent.
[0036] The solvent is composed of ethyl acetate, dipropylene glycol dimethyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, and deionized water in a mass ratio of 30:15:15:18:40.
[0037] Activated graphene was prepared by the following steps: 5g of tetraethyl orthosilicate was added to 100g of 70% ethanol aqueous solution and stirred until homogeneous. 10g of titanium dioxide-supported graphene was added to the solution. The pH of the system was adjusted to 8-9 using ammonia. The solution was stirred at 40℃ for 20h at a stirring speed of 600r / min. 2g of KH-550 coupling agent was added to the solution. The solution was stirred at 60℃ for another 2h. The solution was then centrifuged, washed, and vacuum dried.
[0038] Titanium dioxide-supported graphene was prepared by the following steps: 8g of graphene oxide was added to 100g of deionized water and ultrasonically treated for 40min at a frequency of 80kHz. 3g of nano-titanium dioxide was added and stirred at 70℃ for 2h at a stirring speed of 500r / min. The mixture was then added to a high-pressure reactor and hydrothermally treated at 220℃ for 20h. After cooling to room temperature, the mixture was centrifuged, washed, and freeze-dried. The mixture was then kept at 800℃ for 30min under an argon atmosphere and cooled to room temperature.
[0039] The preparation method of the above-mentioned stealth coating includes the following steps: adding activated graphene and polycarboxylate dispersant to a solvent and stirring at 1500 r / min for 15 min to obtain a premix; adding aliphatic polyurethane resin, room temperature vulcanized phenyl silicone rubber, silane coupling agent KH-560, hollow phenolic microspheres, boron nitride nanosheets, magnetic nanoferrite, and nano silicon carbide to the premix and stirring at 500 r / min for 40 min; sequentially adding wetting agent, organosilicon defoamer, trichloroethyl phosphate, and dimethyldimethoxysilane and stirring at 500 r / min for 40 min; and passing the mixture through a 200-mesh sieve.
[0040] Example 3 A stealth coating comprises the following raw materials: 45g aliphatic polyurethane resin, 25g room temperature vulcanized phenyl silicone rubber, 1.2g silane coupling agent KH-560, 4g hollow phenolic microspheres, 1.5g boron nitride nanosheets, 1.8g magnetic nanoferrite, 1.3g nano silicon carbide, 15g activated graphene, 1.2g wetting agent, 1.7g organosilicon defoamer, 1.3g trichloroethyl phosphate, 4g dimethyldimethoxysilane, 1.5g polycarboxylate dispersant, and 100g solvent.
[0041] The solvent is composed of ethyl acetate, dipropylene glycol dimethyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, and deionized water in a mass ratio of 28:8:12:12:35.
[0042] Activated graphene was prepared by the following steps: 2g of tetraethyl orthosilicate was added to 90g of 55% ethanol aqueous solution and stirred until homogeneous. 9g of titanium dioxide-supported graphene was added to the solution. The pH of the system was adjusted to 8-9 using ammonia. The solution was stirred at 33℃ for 18h at a stirring speed of 400r / min. 1.7g of KH-550 coupling agent was added to the solution. The solution was stirred at 52℃ for 100min. The solution was then centrifuged, washed, and vacuum dried.
[0043] Titanium dioxide-supported graphene was prepared by the following steps: 5g of graphene oxide was added to 80g of deionized water and ultrasonically treated for 25min at a frequency of 78kHz. 1.5g of nano-titanium dioxide was added and stirred at 68℃ for 80min at a stirring speed of 450r / min. The mixture was then added to a high-pressure reactor and hydrothermally treated at 205℃ for 18h. After cooling to room temperature, the mixture was centrifuged, washed, and freeze-dried. The solution was then kept at 720℃ for 25min under an argon atmosphere and cooled to room temperature.
[0044] The preparation method of the above-mentioned stealth coating includes the following steps: adding activated graphene and polycarboxylate dispersant to a solvent and stirring at 800 r / min for 12 min to obtain a premix; adding aliphatic polyurethane resin, room temperature vulcanized phenyl silicone rubber, silane coupling agent KH-560, hollow phenolic microspheres, boron nitride nanosheets, magnetic nanoferrite, and nano silicon carbide to the premix and stirring at 300 r / min for 35 min; sequentially adding wetting agent, organosilicon defoamer, trichloroethyl phosphate, and dimethyldimethoxysilane and stirring at 300 r / min for 35 min; and passing the mixture through a 200-mesh sieve.
[0045] Example 4 A stealth coating comprises the following raw materials: 55g aliphatic polyurethane resin, 15g room temperature vulcanized phenyl silicone rubber, 1.8g silane coupling agent KH-560, 2g hollow phenolic microspheres, 2.5g boron nitride nanosheets, 1.2g magnetic nanoferrite, 1.7g nano silicon carbide, 5g activated graphene, 1.8g wetting agent, 1.3g organosilicon defoamer, 1.7g trichloroethyl phosphate, 2g dimethyldimethoxysilane, 1.5g polycarboxylate dispersant, and 140g solvent.
[0046] The solvent is composed of ethyl acetate, dipropylene glycol dimethyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, and deionized water in a mass ratio of 22:12:8:16:25.
[0047] Activated graphene was prepared by the following steps: 4g of tetraethyl orthosilicate was added to 70g of 65% ethanol aqueous solution and stirred until homogeneous. 7g of titanium dioxide-supported graphene was added to the solution. The pH of the system was adjusted to 8-9 using ammonia. The solution was stirred at 37℃ for 12h at a stirring speed of 500r / min. 1.3g of KH-550 coupling agent was added to the solution. The solution was stirred at 58℃ for another 80min. The solution was then centrifuged, washed, and vacuum dried.
[0048] Titanium dioxide-supported graphene was prepared by the following steps: 7g of graphene oxide was added to 60g of deionized water and ultrasonically treated for 35min at a frequency of 72kHz. 2.5g of nano-titanium dioxide was added and stirred at 62℃ for 100min at a stirring speed of 350r / min. The mixture was then added to a high-pressure reactor and hydrothermally treated at 215℃ for 12h. After cooling to room temperature, the mixture was centrifuged, washed, and freeze-dried. It was then kept at 780℃ for 15min under an argon atmosphere and cooled to room temperature.
[0049] The preparation method of the above-mentioned stealth coating includes the following steps: adding activated graphene and polycarboxylate dispersant to a solvent and stirring at 1200 r / min for 8 min to obtain a premix; adding aliphatic polyurethane resin, room temperature vulcanized phenyl silicone rubber, silane coupling agent KH-560, hollow phenolic microspheres, boron nitride nanosheets, magnetic nanoferrite, and nano silicon carbide to the premix and stirring at 400 r / min for 25 min; sequentially adding wetting agent, organosilicon defoamer, trichloroethyl phosphate, and dimethyldimethoxysilane and stirring at 400 r / min for 25 min; and passing the mixture through a 200-mesh sieve.
[0050] Example 5 A stealth coating comprises the following raw materials: 50g aliphatic polyurethane resin, 20g room temperature vulcanized phenyl silicone rubber, 1.5g silane coupling agent KH-560, 3g hollow phenolic microspheres, 2g boron nitride nanosheets, 1.5g magnetic nanoferrite, 1.5g nano silicon carbide, 10g activated graphene, 1.5g wetting agent, 1.5g organosilicon defoamer, 1.5g trichloroethyl phosphate, 3g dimethyldimethoxysilane, 1.5g polycarboxylate dispersant, and 120g solvent.
[0051] The solvent is composed of ethyl acetate, dipropylene glycol dimethyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, and deionized water in a mass ratio of 25:10:10:14:30.
[0052] Activated graphene was prepared by the following steps: 3g of tetraethyl orthosilicate was added to 80g of 60% ethanol aqueous solution and stirred until homogeneous. 8g of titanium dioxide-supported graphene was added to the solution. The pH of the system was adjusted to 8-9 using ammonia. The solution was stirred at 35℃ for 15h at a stirring speed of 450r / min. 1.5g of KH-550 coupling agent was added to the solution. The solution was stirred at 55℃ for another 90min. The solution was then centrifuged, washed, and vacuum dried.
[0053] Titanium dioxide-supported graphene was prepared by the following steps: 6g of graphene oxide was added to 70g of deionized water and ultrasonically treated for 30min at a frequency of 75kHz. 2g of nano-titanium dioxide was added and stirred at 65℃ for 90min at a stirring speed of 400r / min. The mixture was then added to a high-pressure reactor and hydrothermally treated at 210℃ for 15h. After cooling to room temperature, the mixture was centrifuged, washed, and freeze-dried. The solution was then kept at 750℃ for 20min under an argon atmosphere and cooled to room temperature.
[0054] The preparation method of the above-mentioned stealth coating includes the following steps: adding activated graphene and polycarboxylate dispersant to a solvent and stirring at 1000 r / min for 10 min to obtain a premix; adding aliphatic polyurethane resin, room temperature vulcanized phenyl silicone rubber, silane coupling agent KH-560, hollow phenolic microspheres, boron nitride nanosheets, magnetic nanoferrite, and nano silicon carbide to the premix and stirring at 350 r / min for 30 min; sequentially adding wetting agent, organosilicon defoamer, trichloroethyl phosphate, and dimethyldimethoxysilane and stirring at 350 r / min for 30 min; and passing the mixture through a 200-mesh sieve.
[0055] Comparative Example 1 A stealth coating comprises the following raw materials: 50g aliphatic polyurethane resin, 20g room temperature vulcanized phenyl silicone rubber, 1.5g silane coupling agent KH-560, 3g hollow phenolic microspheres, 2g boron nitride nanosheets, 1.5g magnetic nanoferrite, 1.5g nano silicon carbide, 8.07g activated graphene, 1.93g nano titanium dioxide, 1.5g wetting agent, 1.5g silicone defoamer, 1.5g trichloroethyl phosphate, 3g dimethyldimethoxysilane, 1.5g polycarboxylate dispersant, and 120g solvent.
[0056] The solvent is composed of ethyl acetate, dipropylene glycol dimethyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, and deionized water in a mass ratio of 25:10:10:14:30.
[0057] Activated graphene was prepared by the following steps: 3g of tetraethyl orthosilicate was added to 80g of 60% ethanol aqueous solution and stirred until homogeneous. 6g of reduced graphene was added, and the pH of the system was adjusted to 8-9 with ammonia. The mixture was stirred at 35℃ for 15h at a stirring speed of 450r / min. 1.5g of KH-550 coupling agent was added, and the mixture was stirred at 55℃ for another 90min. The mixture was then centrifuged, washed, and vacuum dried.
[0058] Reduced graphene was prepared by the following steps: 6g of graphene oxide was kept at 750℃ for 20min in an argon atmosphere and then cooled to room temperature.
[0059] The preparation method of the above-mentioned stealth coating includes the following steps: adding activated graphene and polycarboxylate dispersant to a solvent and stirring at 1000 r / min for 10 min to obtain a premix; adding aliphatic polyurethane resin, room temperature vulcanized phenyl silicone rubber, silane coupling agent KH-560, hollow phenolic microspheres, boron nitride nanosheets, magnetic nanoferrite, and nano silicon carbide to the premix and stirring at 350 r / min for 30 min; sequentially adding wetting agent, organosilicon defoamer, trichloroethyl phosphate, and dimethyldimethoxysilane and stirring at 350 r / min for 30 min; and passing the mixture through a 200-mesh sieve.
[0060] Comparative Example 2 A stealth coating comprises the following raw materials: 50g aliphatic polyurethane resin, 20g room temperature vulcanized phenyl silicone rubber, 1.5g silane coupling agent KH-560, 3g hollow phenolic microspheres, 2g boron nitride nanosheets, 1.5g magnetic nanoferrite, 1.5g nano silicon carbide, 9.17g activated graphene, 0.83g silicon dioxide, 1.5g wetting agent, 1.5g organosilicon defoamer, 1.5g trichloroethyl phosphate, 3g dimethyldimethoxysilane, 1.5g polycarboxylate dispersant, and 120g solvent.
[0061] The solvent is composed of ethyl acetate, dipropylene glycol dimethyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, and deionized water in a mass ratio of 25:10:10:14:30.
[0062] Activated graphene was prepared by the following steps: 8g of titanium dioxide-supported graphene was added to 80g of 60% ethanol aqueous solution and stirred until homogeneous. The pH of the system was adjusted to 8-9 using ammonia. The mixture was stirred at 35℃ for 15h at a stirring speed of 450r / min. 1.5g of KH-550 coupling agent was added, and the mixture was stirred at 55℃ for another 90min. The mixture was then centrifuged, washed, and vacuum dried.
[0063] Titanium dioxide-supported graphene was prepared by the following steps: 6g of graphene oxide was added to 70g of deionized water and ultrasonically treated for 30min at a frequency of 75kHz. 2g of nano-titanium dioxide was added and stirred at 65℃ for 90min at a stirring speed of 400r / min. The mixture was then added to a high-pressure reactor and hydrothermally treated at 210℃ for 15h. After cooling to room temperature, the mixture was centrifuged, washed, and freeze-dried. The solution was then kept at 750℃ for 20min under an argon atmosphere and cooled to room temperature.
[0064] The preparation method of the above-mentioned stealth coating includes the following steps: adding activated graphene and polycarboxylate dispersant to a solvent and stirring at 1000 r / min for 10 min to obtain a premix; adding aliphatic polyurethane resin, room temperature vulcanized phenyl silicone rubber, silane coupling agent KH-560, hollow phenolic microspheres, boron nitride nanosheets, magnetic nanoferrite, and nano silicon carbide to the premix and stirring at 350 r / min for 30 min; sequentially adding wetting agent, organosilicon defoamer, trichloroethyl phosphate, and dimethyldimethoxysilane and stirring at 350 r / min for 30 min; and passing the mixture through a 200-mesh sieve.
[0065] The stealth coatings obtained in Example 5 and Comparative Examples 1-3 were applied to the surface of tent fabric (polyester fabric) with a coating thickness of 0.5 mm. They were dried at room temperature for 1-2 days, then placed in a 75°C oven for 3 hours and cooled to room temperature to form a stealth coating.
[0066] (1) Radar stealth performance test: The above-mentioned stealth coating fabric was cut into square samples of 1.5m × 1.5m (ensuring neat edges). The samples were fixed flat on a high-strength test bracket using clamps to ensure that the samples were wrinkle-free and undisturbed during the test. A high-performance vector network analyzer was used, with the transmission frequency range set to 0.3~20GHz and the frequency scan step size set to 0.05GHz to obtain more accurate RCS data. The transmission power was set to 15dBm to ensure that the signal strength could effectively detect the samples without damaging them. The transmitting antenna and receiving antenna were located on both sides of the turntable, forming a 45° angle with the samples, and the antenna distance from the samples was 5m. The turntable rotated at a constant speed of 1° / s to simulate the situation where the target was detected by radar at different angles. During the rotation, the vector network analyzer recorded the RCS values of the samples at different frequencies and angles in real time, and the average value was taken as the radar stealth performance index of the samples.
[0067] like Figure 1 As shown, the stealth coating formed using the stealth coating obtained in Example 5 has the lowest average RCS value, which is significantly better than the comparative example.
[0068] (2) Infrared stealth performance test: The sample was placed in a constant temperature and humidity environment of 25℃ and 50% relative humidity for 2 hours to allow the sample to reach thermal equilibrium and eliminate the influence of environmental factors on the test results. An infrared thermal imager was used to take pictures at a distance of 1m from the sample, ensuring that the thermal imager lens was vertically aligned with the center of the sample. The resolution of the thermal imager was set to 640×480, which can clearly capture the subtle temperature differences on the sample surface. Emissivity measurement: The infrared emissivity of the sample in the 8-14μm band was measured using a Fourier transform infrared spectrometer. The number of scans was set to 64. The resolution was set to 2cm. -1 It can accurately distinguish the emissivity changes of a sample in this wavelength band.
[0069] like Figure 2 As shown, the stealth coating formed using the stealth coating obtained in Example 5 has the lowest infrared emissivity, which is significantly better than the comparative example.
[0070] (3) Service life test: The sample was installed on the abrasion testing machine, and the friction pressure was set to 500g to simulate the friction force in actual use. The friction frequency was 100 times / minute to accelerate the wear rate. At the same time, ultraviolet irradiation was simulated using a power of 100W / m 2 An ultraviolet lamp was placed 30cm away from the sample to simulate outdoor sunlight. Rainwater spray was set at a rate of 1L / min to simulate a rainy environment. Sample inspection: The test was stopped every 50 hours, and the sample surface was carefully inspected. When the average stealth performance decreased by more than 30%, the test time at this point was recorded as the sample's lifespan.
[0071] like Figure 3 As shown, the stealth coating formed using the stealth coating obtained in Example 5 has the longest service life, which is significantly better than that of the comparative example.
[0072] The reason for the above results is that this invention utilizes the silica coating layer on the surface of activated graphene to achieve a gradual matching with the internal titanium dioxide, enabling radar waves to be efficiently coupled into the material's interior, thus improving the absorption efficiency of electromagnetic waves over a wide frequency band. The internally loaded titanium dioxide and magnetic nickel-zinc ferrite form an electromagnetic loss network, which further dissipates wide-frequency (2-18 GHz) electromagnetic energy through dielectric polarization and hysteresis loss, significantly improving the absorption efficiency. This invention uses hollow phenolic microspheres as low-density, high-porosity structural units, which, in synergy with activated graphene, construct wave-transparent channels in the coating, allowing some incident radar waves to penetrate the coating instead of being reflected, reducing the overall radar scattering cross-section. In the infrared band, phenyl silicone rubber, boron nitride nanosheets, and nano-silicon carbide work synergistically to effectively reduce the infrared emissivity of the coating. This invention enables most of the radar wave energy in the coating to be absorbed by the internal loss network, with a small portion transmitted through the microspheres and activated graphene, while reflection is suppressed; infrared radiation is effectively blocked, achieving spatial separation and functional decoupling of electromagnetic response, and achieving synergistic enhancement of broadband wave absorption and infrared stealth.
[0073] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A stealth coating, characterized in that, The raw materials, by weight, include: 40-60 parts aliphatic polyurethane resin, 10-30 parts room temperature vulcanized phenyl silicone rubber, 1-2 parts silane coupling agent, 1-5 parts hollow phenolic microspheres, 1-3 parts infrared reflection enhancer, 1-2 parts magnetic nano ferrite, 1-2 parts nano silicon carbide, 7-17 parts activated graphene, 1-2 parts wetting agent, 1-2 parts defoamer, 1-2 parts plasticizer, 1-5 parts crosslinking agent, 1-2 parts dispersant, and 80-150 parts solvent. The infrared reflectance enhancer is boron nitride nanosheets with a particle size of 100-300 nm; the magnetic nanoferrite is NiZnFe2O4 with a particle size of 100-500 nm. Activated graphene is obtained by loading graphene with titanium dioxide and mixing it with tetraethyl orthosilicate and a silane coupling agent in an alkaline environment.
2. The stealth coating according to claim 1, characterized in that, The defoamer is an organosilicone defoamer; the plasticizer is a phosphate ester plasticizer.
3. The stealth coating according to claim 1, characterized in that, The crosslinking agent is a silanol condensation type crosslinking agent; the dispersant is a polycarboxylate dispersant.
4. The stealth coating according to claim 1, characterized in that, The crosslinking agent is dimethyldimethoxysilane.
5. The stealth coating according to claim 1, characterized in that, The solvents include: ethyl acetate, dipropylene glycol dimethyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, and water; the mass ratio of ethyl acetate, dipropylene glycol dimethyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, and water is 20-30:5-15:5-15:10-18:20-40.
6. The stealth coating according to claim 1, characterized in that, Activated graphene is prepared by the following steps: Tetraethyl orthosilicate is added to an aqueous ethanol solution and stirred until homogeneous. Titanium dioxide-supported graphene is added to the solution, and the pH of the system is adjusted to 8-9. The solution is stirred at 30-40℃ for 10-20 hours. Then, a silane coupling agent is added to the solution, and the solution is stirred at 50-60℃ for 1-2 hours. The solution is then centrifuged, washed, and vacuum dried.
7. The stealth coating according to claim 6, characterized in that, The silane coupling agent is KH-550; the mass ratio of tetraethyl orthosilicate, titanium dioxide-supported graphene, and silane coupling agent is 1-5:5-10:1-2.
8. The stealth coating according to claim 6, characterized in that, Titanium dioxide-supported graphene is prepared by the following steps: graphene oxide is added to water and ultrasonically treated for 20-40 minutes, nano-titanium dioxide is added, stirred at 60-70℃ for 1-2 hours, hydrothermally treated at 200-220℃ for 10-20 hours, cooled to room temperature, centrifuged, washed, and freeze-dried; then kept at 700-800℃ for 10-30 minutes in an argon atmosphere and cooled to room temperature.
9. The stealth coating according to claim 8, characterized in that, The mass ratio of graphene oxide to nano-titanium dioxide is 4-8:1-3.
10. A method for preparing a stealth coating as described in any one of claims 1-9, characterized in that, The process includes the following steps: adding activated graphene and dispersant to a solvent and stirring for 5-15 minutes to obtain a premix; adding aliphatic polyurethane resin, room temperature vulcanized phenyl silicone rubber, silane coupling agent, hollow phenolic microspheres, infrared reflection enhancer, magnetic nano ferrite, and nano silicon carbide to the premix and stirring for 20-40 minutes; then adding wetting agent, defoamer, plasticizer, and crosslinking agent in sequence and stirring for 20-40 minutes, followed by sieving.
Citation Information
Patent Citations
Graphene-titanium dioxide nanotube composite material and preparation method thereof
CN102496700A
Graphene-silicon electromagnetic shielding filler and electromagnetic shielding coating
CN108117811A